2013
DOI: 10.1681/asn.2013020148
|View full text |Cite
|
Sign up to set email alerts
|

ABIN1 Dysfunction as a Genetic Basis for Lupus Nephritis

Abstract: The genetic factors underlying the pathogenesis of lupus nephritis associated with systemic lupus erythematosus are largely unknown, although animal studies indicate that nuclear factor (NF)-kB is involved. We reported previously that a knockin mouse expressing an inactive form of ABIN1 (ABIN1[D485N]) develops lupus-like autoimmune disease and demonstrates enhanced activation of NF-kB and mitogen-activated protein kinases in immune cells after toll-like receptor stimulation. In the current study, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 63 publications
3
62
0
1
Order By: Relevance
“…These studies have related the roles of ABIN-1 in anti-inflammation to its UBD, likely by targeting the TLR-signaling pathways that control NF-κB and MAPK activity (27)(28)(29)(30). In this study, both bbtABIN1 and bbtABIN2 proteins, when expressed individually, were found to localize in cytoplasm and form unique punctuated spherical structures of various sizes, suggesting that bbtABIN1 and bbtABIN2 may form complexes with other unidentified proteins.…”
Section: Uban Domain Provides the Molecular Basis For Abins To Play Imentioning
confidence: 62%
See 1 more Smart Citation
“…These studies have related the roles of ABIN-1 in anti-inflammation to its UBD, likely by targeting the TLR-signaling pathways that control NF-κB and MAPK activity (27)(28)(29)(30). In this study, both bbtABIN1 and bbtABIN2 proteins, when expressed individually, were found to localize in cytoplasm and form unique punctuated spherical structures of various sizes, suggesting that bbtABIN1 and bbtABIN2 may form complexes with other unidentified proteins.…”
Section: Uban Domain Provides the Molecular Basis For Abins To Play Imentioning
confidence: 62%
“…In addition to connecting A20 to NEMO to affect NF-κB signaling, as an ubiquitin sensor, a growing number of references have implicated ABIN-1 in embryonic development and in chronic inflammatory and autoimmune diseases, such as psoriasis, rheumatoid arthritis, and lupus nephritis (27)(28)(29). These studies have related the roles of ABIN-1 in anti-inflammation to its UBD, likely by targeting the TLR-signaling pathways that control NF-κB and MAPK activity (27)(28)(29)(30).…”
Section: Uban Domain Provides the Molecular Basis For Abins To Play Imentioning
confidence: 99%
“…The mutant B cells also proliferate more rapidly in response to TLR ligands (Nanda et al, 2011). The ABIN(D485N)-expressing mice develop all the hallmarks of autoimmunity and succumb to a disease that resembles Type III and Type IV lupus in humans, termed lupus nephritis (Nanda et al, 2011;Caster et al, 2013). Interestingly, polymorphisms in the human gene encoding ABIN1 predispose individuals to several autoimmune diseases (Han et al, 2009;Nair et al, 2009;He et al, 2010;Gregersen et al, 2012;Yang et al, 2013).…”
Section: How the Signalling Network Is Activated Formation Of The Mydmentioning
confidence: 99%
“…HLA-DR2/DR3 , STAT4 , IRF5/IRF7 , IFIH1 , ITGAM and UBE2L3 ) [78] and/or renal disorders (e.g. ITGAM , STAT4 , TNFSF4, TNFAIP3 and TNIP1 ) [79,80]. In addition, the apolipoprotein L1 nephropathy risk alleles G1/G2 strongly impact the risk and the time of end-stage renal disease (ESRD) in African Americans with lupus nephritis (LN), which may partly explain the increased risk of LN-ESRD in African Americans due to the high frequency of these alleles in African Americans but near absence in European Americans [81].…”
Section: Connecting Genotype To Phenotype In Slementioning
confidence: 99%